1995
DOI: 10.1200/jco.1995.13.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

CD30/Ki-1-positive lymphoproliferative disorders of the skin--clinicopathologic correlation and statistical analysis of 86 cases: a multicentric study from the European Organization for Research and Treatment of Cancer Cutaneous Lymphoma Project Group.

Abstract: Our findings indicate that CD30+ cutaneous lymphoproliferative disorders comprise a spectrum of closely related skin lesions, which can be assigned a relatively favorable or unfavorable prognosis by a combined clinical and pathologic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
2
9

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(167 citation statements)
references
References 50 publications
5
151
2
9
Order By: Relevance
“…Primary cutaneous CD30+ ALCLs uniformly lack the t(2;5) and ALK expression (13). Despite this, they usually have a favourable prognosis and are highly responsive to external radiotherapy and cytotoxic chemotherapy (either alone or in combination) (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cutaneous CD30+ ALCLs uniformly lack the t(2;5) and ALK expression (13). Despite this, they usually have a favourable prognosis and are highly responsive to external radiotherapy and cytotoxic chemotherapy (either alone or in combination) (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…94,[245][246][247] It has been suggested that LyP is a precursor lesion of primary cutaneous ALCL. The studies summarized in Table 12 indicate that the t(2;5) NPM-ALK is Leukemia absent in LyP (except for one study) and rare in most studies on primary cutaneous CD30 + ALCL.…”
Section: Incidence Of Npm-alk In Primary Cutaneous Alcl and Lymphomatmentioning
confidence: 99%
“…The relationship between these entities is supported by the conversion of LyP to CD30-positive ALCL in a minority of cases (1,5). In contrast, there is mounting evidence that noncutaneous CD30-positive ALCL, although morphologically similar to its cutaneous counterpart, is biologically distinct.…”
Section: Discussionmentioning
confidence: 97%
“…Criteria for the histologic distinction between these two entities are imprecise, at times causing a diagnostic dilemma. Ultimately, LyP and PC CD30-positive ALCL have both histologic and clinical overlap, prompting some to consider these entities as ends of a spectrum of PC CD30-positive LPDs (1,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation